Experiment and Dynamic Characteristic Analysis of Double Pitch Time Sharing Meshing Silent Chain - Ding Song; Yang Shuchen; Zhang Xiaoqi; Gu Dongwei; Shao Guiyang; Jiang Donglin (Jixie chuandong)
In order to improve the transportation performance and reliability of chain conveyor,based on the silent chain meshing mechanism,a double pitch time sharing meshing silent chain is designed,and the related design parameters are given. Base on the ADAMS,a simulation model is established to compare with the tight edge fluctuation and meshing impact force of double pitch time share meshing silent chain and double pitch roller chain. As the result of the stimulation analysis shows,compared with double pitch roller chain,the meshing of double pitch time share meshing silent chain is stable and the tight edge fluctuation is reduced by 59%,while meshing impact force is reduced by 51. 9%. Then it is compared with results of bench test,on the confined fluid chain bench,the noise test and the 250 h wear test are conducted,compared with that of double pitch roller chain,the average noise at the tight side mesh point of double pitch time share meshing silent chain is reduced by 4. 6 d B and the wear elongation is reduced by 0. 28%. The experimental results prove that the rationality of double pitch time share meshing silent chain design is reasonable.